Use of a National Continuing Medical Education Meeting to Provide Simulation-Based Training in Temporary Hemodialysis Catheter Insertion Skills: A Pre-Test Post-Test Study. Issue 1 (14th October 2014) - Clark, Edward G; Paparello, James J; Wayne, Diane B; Edwards, Cedric; Hoar, Stephanie; McQuillan, Rory; Schachter, Michael E; Barsuk, Jeffrey H
Background: Simulation-based-mastery-learning (SBML) is an effective method to train nephrology fellows to competently insert temporary, non-tunneled hemodialysis catheters (NTHCs). Previous studies of SBML for NTHC-insertion have been conducted at a local level. Objectives: Determine if SBML for NTHC-insertion can be effective when provided at a national continuing medical education (CME) meeting. Describe the correlation of demographic factors, prior experience with NTHC-insertion and procedural self-confidence with simulated performance of the procedure. Design: Pre-test – post-test study. Setting: 2014 Canadian Society of Nephrology annual meeting. Participants: Nephrology fellows, internal medicine residents and medical students. Measurements: Participants were surveyed regarding demographics, prior NTHC-insertion experience, procedural self-confidence and attitudes regarding the training they received. NTHC-insertion skills were assessed using a 28-item checklist. Methods: Participants underwent a pre-test of their NTHC-insertion skills at the internal jugular site using a realistic patient simulator and ultrasound machine. Participants then had a training session that included a didactic presentation and 2 hours of deliberate practice using the simulator. On the following day, trainees completed a post-test of their NTHC-insertion skills. All participants were required to meet or exceed a minimum passing score (MPS) previously set at 79%. Trainees who did not reach the MPS were required to perform more deliberate practice until the MPS was achieved. Results: Twenty-two individuals participated in SBML training. None met or exceeded the MPS at baseline with a median checklist score of 20 (IQR, 7.25 to 21). Seventeen of 22 participants (77%) completed post-testing and improved their scores to a median of 27 (IQR, 26 to 28; p < 0.001). All met or exceeded the MPS on their first attempt. There were no significant correlations between demographics, prior experience or procedural self-confidence with pre-test performance. Limitations: Small sample-size and self-selection of participants. Costs could limit the long-term feasibility of providing this type of training at a CME conference. Conclusions: Despite most participants reporting having previously inserted NTHCs in clinical practice, none met the MPS at baseline; this suggests their prior training may have been inadequate.